Control of Nanoparticle Release by Membrane Composition for Dual-Responsive Nanocapsules - Liu, Xiaoling; Wang, Xueyi; Voit, Brigitte; Appelhans, Dietmar (Chemistry - A European Journal, 2019)
Stimulus-responsive polymeric nanocapsules usable as cell mimics can be engineered to precisely control cargo release. This work reports the release behavior of post-loaded nanoparticles through permeable membranes of stable pH and temperature dual-responsive polymeric nanocapsules (CP1, CP2, and CP3) with the same membrane thickness but different membrane composition, prepared by layer-by-layer assembly and surface-initiated single electron transfer living radical polymerization, respectively. These nanocapsules differ in their tunable membrane permeability for post-loaded nanoparticles as protein mimics, tailored by pH and temperature stimuli. Release mechanisms are dominated by membrane composition, such as polyelectrolyte multilayer membrane for CP1, pure cationic membrane for CP2, and valve-like functions for CP3. Thus, one can postulate the main locations of post-loaded protein mimics in the different nanocapsules. Understanding the post-loading and diffusion mechanism of nanoparticles through permeable membranes in cell mimics paves the way for the construction of new “smart” synthetic protocells with control over the exchange of bioactive nanoparticles between different compartments.
CRIS-Team Scopus Importer:2022-04-14
Keywords: cargo post-loading; cargo release; cell mimics; membranes; nanocapsules; nanotechnology